Switching the paradigm in academic literacy: from a normative to a transformative insight in academic writing - Antonio Esquicha Medina (Pontificia Universidad Católica del Perú, 2022)
Academic literacy in a second language (L2) is a competence required by current society in academic and professional fields. However, perspectives have changed throughout the years in order to comply with the requirements of modern society; challenging academic writing standards. Therefore, an ample and inclusive comprehension that informs current practices occurring worldwide, where English is considered a lingua franca for communication, is required. This systematic literature review aims to describe an overview of paradigms towards academic writing as a continuum, integrating both traditional and current literacy practices throughout a revision of empirical studies conducted in this area. To conclude, switching from traditional normative approaches to more transformative ones, under the scope of New Literacy Studies and longitudinal studies, is suggested as an alternative towards academic literacy in English in L2.